Research as relationship: engaging with ethical intent. Issue 3 (4th May 2017) - Shordike, Anne; Hocking, Clare; Bunrayong, Wannipa; Vittayakorn, Soisuda; Rattakorn, Phuanjai; Pierce, Doris; Wright-St Clair, Valerie A.
Abstract: This international research collaborative undertook what became a decade long process to look at meanings of celebratory food related occupations of elder women across three cultures in New Zealand, Thailand and the United States. Cross-cultural research comes with inherent ethical issues related to cultural lenses, use of instruments and potential biases of investigators. The many views of what cross cultural research is and how it might be done and the very general ethical codes from professional institutions provided guidance for protections of participants, however, gave little direction regarding ethical interaction amongst researchers. The team was committed to open, interpretive and unbiased engagement with each other, study participants and data. Critical engagement supported this, including the development of methodology to assure trustworthiness of data interpretation and creation of in person and virtual communication strategies to give all cultures voice. We found ways to negotiate language barriers and collaborated to deal with inequity in resources. We consciously addressed issues of equitable distribution of labor and authorship. We educated each other about our cultures by design and circumstance. Our satisfaction with the research process and outcomes is directly related to our adherence to its basic integrity.